2014
DOI: 10.1002/app.41680
|View full text |Cite
|
Sign up to set email alerts
|

In situ fibrillation of polypropylene/polyamide 6 blends: Effect of organoclay addition

Abstract: In situ fibrillation of PP/PA6 blends (85/15 wt %) is investigated in presence of two kinds of organically modified montmorillonite, differing by the polarity of their surfactant. The organoclay is primary dispersed either in the PP (for the low-polarity Cloisite V R 15A) or in the PA6 (for the high-polarity Cloisite V R 30B), according to its assumed affinity. In absence of organoclay, a fibrillar morphology is achieved after the melt-blending and hot-stretching step, as evidenced by SEM analysis. Upon clay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…and Table ) and the viscosities of the dispersed phase and the matrix , ηdispersed phase=4555 Pas and ηmatrix=339.8 Pas, a value of α = 3.8 mN/m is obtained for the interfacial tension of our PP/PA blend. This value is closer to α = 5 mN/m, found by Chomat et al for PP/PA6 blends at T = 240 °C, but is lower than α = 9 mN/m reported by Shi et al for PP/PA6 blends at T = 230 °C, determined using the Palierne method. Comparatively, other literature results show that the interfacial tension of PP/PA6 blends is considerably reduced, down to α = 3 mN/m at T = 230 °C, when maleated polypropylenes were used as compatibilizers.…”
Section: Resultssupporting
confidence: 75%
“…and Table ) and the viscosities of the dispersed phase and the matrix , ηdispersed phase=4555 Pas and ηmatrix=339.8 Pas, a value of α = 3.8 mN/m is obtained for the interfacial tension of our PP/PA blend. This value is closer to α = 5 mN/m, found by Chomat et al for PP/PA6 blends at T = 240 °C, but is lower than α = 9 mN/m reported by Shi et al for PP/PA6 blends at T = 230 °C, determined using the Palierne method. Comparatively, other literature results show that the interfacial tension of PP/PA6 blends is considerably reduced, down to α = 3 mN/m at T = 230 °C, when maleated polypropylenes were used as compatibilizers.…”
Section: Resultssupporting
confidence: 75%
“…In the longitudinal direction (Figure 2a'), an heterogeneous discontinuous fibrillar morphology is observed which is attributed to the viscosity difference between the PLA and PA11 [24]. Whatever the observation direction, the interface between PA11 and PLA seems to be weak, a clear gap between the PLA matrix and the PA11 domains being clearly observed.…”
Section: Morphologymentioning
confidence: 95%
“…. Both ratios increase upon CNT addition which could only lead to significant difficulties in dispersion . The selective localization of CNTs in the dispersed phase has caused a dramatic increase in the viscosity and elasticity ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the quality of dispersion has reduced. If CNTs were located in the matrix, they might have performed like compatibilizers and improve the dispersion quality by reducing the aforementioned ratios .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation